Barriers in Adopting Technological Innovation, Organizational Capacity, and Business Environment into Iraq SMEs: A preliminary Study - Mishaal, Mohammed Faraj; Ho Fu Haw (Research Progress in Mechanical and Manufacturing Engineering, 2022)
A successful Small and Medium Sized Enterprise (SME) is highly depends on the performance of innovation business environment, technology adoption, and organizational capacity of a company. This study is aims to identify the barriers to influence the growth of SMEs in the aspect of product innovation, and next, these factors were used to evaluate its interconnection with business practices, technology utilization, and capacity building in relation to growth SMEs’. Furthermore, the insight views of innovative development in a fast-growing market (the macro-environmental viewpoint) are discussed, which give a bigger picture and understanding of SME’s capability to innovate and grow. In this study the data was gathered by using an online questionnaire which consisted of 41 questions. The proposed questionnaire contains of five sections, (a- General information about the company; b- Barriers to SMEs‘Growth; c- Support for SMEs‘; d- Motivation of innovation/open innovation; e- Growth in comparison to competitors). SPSS software was used to analyze the variables relationships. The obtained results indicate that both innovation and open innovation have moderate and somehow strong positive correlation relation with growth and innovativeness SMEs. For future research, more similar cases in terms of innovativeness and growth process are needed to confirm the research conclusions.